Analysis Of Hifz Al-Mal in Maqasid Al-Shari’ah Against the Article “Criminal Act of Corruption” In The Criminal Code of Indonesia - Sanuri, Sanuri (Al-Jinayah : Jurnal Hukum Pidana Islam, 2022)
several points in the Criminal Code (KUHP) which are considered controversial. The theme above will be broken down through several important features in the theory of maqasid al-shari'ah, namely: (1) the principle of maslahah in the rubber article of corruption; (2) reduction of criminal penalties for corruptors in the lens of hifz al-nafs; (3) corruption as an extraordinary crime vs. hifz al-mal; (4) distance the deterrent effect and benefit corruptors from the perspective of hifz al-mal; and (5) daruriyyah level for the Corruption Perception Index (CPI) in Indonesia. In this study, data were obtained through documentation techniques while still based on a deductive mindset and a descriptive-critical-analysis model. The results of the study explain that the spirit of novelty in the Criminal Code in Indonesia is directly proportional to the spirit of realizing maslahah for all components of the nation and has fulfilled the character of daruriyyah. However, there are still a few problems in the aspects of hifz al-nafs and hifz al-mal because several points of change have not fully reflected the demands of the wider community. Key words: Corruption crime, Criminal Code, hifz al-mal, maqasid al-shari’ah